The place of social transformation analysis in vulnerability assessment for climate adaptation planning in Upper West Region, Ghana: a review synthesis - Osei-Amponsah, Charity; Quarmine, William; Wahabu, E. (Wiley, 2023)
Climate vulnerability could be influenced by transforming demographic, technological, cultural, political and economic factors, which cuts across global, regional, national and local scales. Such social transformations result in positive and negative outcomes, with implications for the adaptive capacities of resource-poor households, especially those headed by women. However, these transformations are usually not integrated in climate vulnerability assessments. Based on insights from a stakeholders’ brainstorming workshop and the synthesis of information from traditional literature review, this paper contributes to better understanding of the intersections of social transformation with climate vulnerabilities in the Upper West Region of Ghana. The review indicates that the region is experiencing social transformation triggered by technological, demographic and cultural factors, with implications for climate resilience building. For example, compared to the last decade, there is now an increased use of mobile phones, resulting in improved access to e-extension and climate-smart agriculture services. At the same time, an emerging trend of land commodification is driving poor households to sell or lease farming lands. Within the context of these transformations, climate vulnerability is still assessed through approaches that mainly focus on a ‘static’ view of the extent of exposure to climate hazards and their impacts on rural livelihoods. A social transformation analysis that promotes a systematic investigation of the transforming factors is proposed as an effective approach for vulnerability assessment in climate adaptation planning. This approach provides critical reflections on, and sustainable resilience interventions for addressing both changing biophysical and social vulnerabilities of rural communities.